New 23-Spirocholestane Derivatives from Ypsilandra thibetica - Xie, Bai-Bo; Chen, Chang-Xiang; Guo, Yong-Hui; Li, Yu-Ye; Liu, Ya-Juan; Ni, Wei; Yang, Liu-Meng; Gong, Ning-Bo; Zheng, Yong-Tang; Wang, Rui-Rui; Lü, Yang; Liu, Hai-Yang (Planta Medica, 2013)
Three new unusual 23-spirocholestane derivatives, ypsilanogenin (1), ypsilanogenin 3-O-β-D-glucopyranoside (2), and 4′-acetylypsilanogenin 3-O-β-D-glucopyranoside (3), were isolated from the whole plants of Ypsilandra thibetica. The structures of compounds 1–3 were deduced by spectroscopic and chemical methods, and the structure of 1 was further confirmed by a single-crystal diffraction analysis. All isolates were evaluated for their inhibitory activities against HIV-1.
Keywords: Ypsilandra thibetica; Liliaceae; 23-spirocholestane glycosides; anti-HIV-1 activity